Efficacy of thrombomodulin for acute exacerbation of idiopathic pulmonary fibrosis and nonspecific interstitial pneumonia: a nonrandomized prospective study - Abe, Mitsuhiro (Drug Des Devel Ther, 2015)
PURPOSE: Acute exacerbation (AE) is an important outcome of idiopathic pulmonary fibrosis (IPF) and nonspecific interstitial pneumonia (NSIP). Recombinant human soluble thrombomodulin (rhTM) is a new drug for the treatment of disseminated intravascular coagulation in Japan. The objective of this study was to evaluate the efficacy of rhTM for AE of IPF/NSIP. METHODS: Twenty-two patients with AE-idiopathic interstitial pneumonia (16 patients with IPF and six patients with NSIP) were enrolled in our study. Among them, eleven patients were treated with rhTM (rhTM group), and eleven patients were treated without rhTM (non-rhTM group). Patients admitted to our hospital prior to December 2013 were treated with rhTM, while those admitted after January 2014 were treated without rhTM. The primary endpoint was mortality at 90 days after AE treatment. The secondary endpoint was the safety of rhTM for AE-IPF/AE-NSIP. In addition, we examined prognostic factors of AE-IPF/AE-NSIP. RESULTS: The mortality rate was significantly lower in the rhTM group than in the non-rhTM group (mortality rate at 90 days: 36% vs 90%, P=0.023; median survival time: not reached vs 15.0 days, P=0.019). A univariate analysis revealed the respiratory rate (hazard ratio [HR] 1.09, 95% confidence interval [CI] 1.00–1.18, P=0.039) and rhTM administration (HR 0.21, 95% CI 0.06–0.77, P=0.013) as predictors of mortality at 90 days, and a multivariate analysis identified rhTM administration (HR 0.025, 95% CI 0.0006–0.94, P=0.046) as an independent predictor of mortality at 90 days. No serious adverse events were observed. CONCLUSION: The administration of rhTM is associated with reductions in mortality in patients with AE-IPF/NSIP, without causing adverse events.